Good deal indices in asset pricing: actuarial and financial implications. (22nd May 2017) - Balbás, Alejandro; Garrido, José; Okhrati, Ramin
Abstract: We integrate into a single optimization problem a risk measure, beyond the variance, and either arbitrage‐free real market quotations or financial pricing rules generated by an arbitrage‐free stochastic pricing model. A sequence of investment strategies such that the couple ( expected return, risk ) diverges to ( + ∞, − ∞ ) will be called a good deal ( GD ). The existence of such a sequence is equivalent to the existence of an alternative sequence of strategies such that the couple ( risk, price ) diverges to ( − ∞, − ∞ ) . Moreover, by appropriately adding the riskless asset, every GD may generate a new one only composed of strategies priced at one. We will see that GD s often exist in practice, and the main objective of this paper will be to measure the GD size. The provided GD indices will equal an optimal ratio between both risk and price, and there will exist alternative interpretations of these indices. They also provide the minimum relative (per dollar) price modification that prevents the existence of GD s. Moreover, they will be a crucial instrument to detect those securities or marketed claims that are over‐ or underpriced. Many classical actuarial and financial optimization problems may generate wrong solutions if the used market quotations or stochastic pricing models do not prevent the existence of GD s. This fact is illustrated in the paper, and we point out how the provided GD indices may be useful to overcome this caveat. Numerical experiments are also included.